Comparison of Random Blood Sugar, Uric Acid, and Cholesterol Levels in Krangkeng Village with Karangjaladri Village, West Java, Indonesia - Hendriani, Rini (Universitas Padjadjaran, Indonesia, 2025)
The prevalence of metabolic diseases has increased over time, especially in Indonesia where 17.5% of the population suffers from metabolic syndrome. Metabolic diseases themselves are related to each other such as diabetes mellitus, gout, and dyslipidemia. One of the causes of metabolic diseases is environmental factors so this research aims to examine whether there was a relationship between metabolic diseases between two villages with different environmental conditions (Krangkeng Village and Karangjaladri Village). Data analysis used IBM SPSS Statistics 25 with random blood glucose, total cholesterol, and uric acid data taken using the Multi-Monitoring System Autocheck 3 in 1. The results of the analysis showed that random blood glucose and uric acid levels in men were greater in Karangjaladri village compared to Krangkeng village with statistically significantly different results. Meanwhile, uric acid in women was also greater in Karangjaladri village compared to Krangkeng village but not statistically different. Total cholesterol levels in Krangkeng village were greater than those in Karangjaladri village with statistically significantly different results. This difference could be caused by differences in daily consumption due to differences in geographic location and the main livelihoods of the two villages, where the majority of the residents of Krangkeng village work as farmers and Karangjaladri village as fishermen. The conclusion appears to be that there was a relationship between metabolic diseases and the environmental factors in the two villages studied.